2014
DOI: 10.6026/97320630010371
|View full text |Cite
|
Sign up to set email alerts
|

Study of rust resistance genes in wheat germplasm with DNA markers

Abstract: Wheat is a vital dietary component for human health and widely consumed in the world. Wheat rusts are dangerous pathogens and contribute serious threat to its production. In present study, PCR-Based DNA Markers were employed to check the rust resistance genes among 20 wheat genotypes and 22 markers were amplified. NTSYS-pc 2.2 was used to calculate genetic diversity and Nei and Li's coefficients ranged from 0.55 to 0.95. Cluster analysis was obtained using UPGMA (Unweighted Pair Group Method of Arithmetic Aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Similarly, Yao et al (2006) identified a microsatellite marker Xgwm 526 on the chromosome arm 2BL, linked closely with Yr7 locus resistant to wheat stripe rust. Yr18 gene linked to Xbarc 352 primer was present in 16 RILs at molecular level, similar results were reported by Haque et al (2014) that Xgwm 130 is linked to both of Lr34/Yr18 leaf and stripe rust resistance genes. Yr26 gene linked to Xgwm 11 primer was found to be present in 13 RILs, Yr29 gene was present Table 2.…”
Section: Resultssupporting
confidence: 88%
“…Similarly, Yao et al (2006) identified a microsatellite marker Xgwm 526 on the chromosome arm 2BL, linked closely with Yr7 locus resistant to wheat stripe rust. Yr18 gene linked to Xbarc 352 primer was present in 16 RILs at molecular level, similar results were reported by Haque et al (2014) that Xgwm 130 is linked to both of Lr34/Yr18 leaf and stripe rust resistance genes. Yr26 gene linked to Xgwm 11 primer was found to be present in 13 RILs, Yr29 gene was present Table 2.…”
Section: Resultssupporting
confidence: 88%
“…A collection of 54 wheat cultivars and 11 breeding lines from South Africa was screened to identify Sr2 , Sr24 and Sr31 genes using DNA markers [15]. PCR-based DNA markers were used to check rust resistance genes among the 20 wheat genotypes and 22 markers were amplified [16]. Kokhmetova and Atishova [17] studied the presence of Sr genes ( Sr2 , Sr22 , Sr24 , Sr36 , and Sr46 ), which are effective against Ug99 in 88 cultivars of spring soft wheat in Kazakhstan.…”
Section: Introductionmentioning
confidence: 99%
“…Deployment of specific gene combinations provides durable and improved resistance versus using single genes because a single specific gene is subject to become susceptible due to genetic shifts in the pathogen [64]. In our study, nine closely linked markers specific for 5 Yr genes were used to detect the presence of Yr5, Yr10, Yr15, Yr17 and Yr18 genes among the wheat genotypes and evaluate their effect on the resistance to stripe rust.…”
Section: Discussionmentioning
confidence: 99%
“…The 150-bp and 229-bp bands indicated the presence and absence of the Yr18 gene, respectively. Marker analyses indicate that amplification products correspond with the homozygous resistant allele of Lr34/Yr18 gene were detected in 11 wheat entries (Cat# 2, 3,9,13,20,35,54,58,62,64,70), accounting for 15.7% of studied genotypes (Figure S9, Table 1).…”
Section: Identification Of Yr Genes With Molecular Markers and Stripe Rust Resistance In The Sources Of Resistancementioning
confidence: 99%